Middle- to late-Holocene environmental changes in Bajo de la Quinta, NE Patagonia, inferred by palynological records and their relation to human occupation - Marcos, Maria Alejandra (2012)
The north Patagonian region between 38° and 42°S extends along the proximity of two major atmospheric circulation features in South America: the northern border of the southern westerly circulation belt, and the northeast trade wind circulation associated with the subtropical South Atlantic Anticyclone. The influence of this westerly wind system determines the annual and seasonal precipitation regimen in north Patagonia, while the influence of the South Atlantic Anticyclone is more pronounced towards the east. The changing strength of either of these circulation systems has had a strong influence on Holocene environmental change in the region. Palaeoenvironmental changes are inferred from a 500 cm long core from Bajo de la Quinta, (40°55'42"S, 64°20'19"W) by means of pollen, sediment and geomorphological analyses. A dry phase with westerly winds during the middle Holocene, at around 7000-6600 cal. yr BP, is indicated by xerophytic/psammophytic vegetation and Patagonian steppe components. Between 6600 and 5200 cal. yr BP the pollen record reflects shrub steppe vegetation and low values of long distance transported pollen indicates little influence of the westerly winds. Between 5200 and 2900 cal. yr BP very arid conditions are indicated by high pollen values of Ephedra sp. and Nassauvia sp. and westerlies influenced by long distance pollen types such as Nothofagus sp. In the late Holocene (2900 cal. yr BP) the pollen record shows an increase in typical shrub taxa of the Monte and Espinal vegetation and low influence of long distance taxa. This may suggest a change to semi-arid conditions that persisted until the present, where the shrub steppe is the dominant vegetation. The environmental and geomorphological changes that occurred during the middle and late Holocene had influenced the space and resources used by hunter-gatherers of the area.